2004
DOI: 10.1097/01.aog.0000109519.74229.30
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Effect of Intrauterine Lidocaine Plus Naproxen Sodium in Endometrial Biopsy

Abstract: I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 11 publications
5
60
2
4
Order By: Relevance
“…The largest trial of NSAIDs prior to IUD insertion used ibuprofen 400 mg, a dose lower than is commonly recommended in the United States [7]. Interestingly, NSAIDs are often recommended prior to other office-based gynecologic procedures, such as colposcopy [8], endometrial biopsy [9] and dilation and curettage [10][11][12], though data are mixed about their effectiveness with these procedures as well.…”
Section: Introductionmentioning
confidence: 99%
“…The largest trial of NSAIDs prior to IUD insertion used ibuprofen 400 mg, a dose lower than is commonly recommended in the United States [7]. Interestingly, NSAIDs are often recommended prior to other office-based gynecologic procedures, such as colposcopy [8], endometrial biopsy [9] and dilation and curettage [10][11][12], though data are mixed about their effectiveness with these procedures as well.…”
Section: Introductionmentioning
confidence: 99%
“…Dogan et al conducted a study in which 120 women became candidate of outpatient endometrial biopsy and assigned to four Local Anesthesia Methods in Outpatient Endometrial Biopsy groups; a group received 5cc of intrauterine 2% lidocaine, and the other three received 550mg oral naproxen, 5cc of intrauterine lidocaine and 550 mg oral naproxen plus intrauterine normal saline. They concluded that intrauterine lidocaine instillation significantly decreases pain of pipelle endometrial when used in combination with oral naproxen sodium; while there was not seen considerable difference in two groups which received lidocaine and naproxen with controlling group (13). As it is declared, the results of different researches in this field were not aligned necessarily.…”
Section: Discussionmentioning
confidence: 98%
“…[12] In another placebocontrolled trial, Dogan et al showed that naproxen when combined with lidocaine was effective in relieving pain during endometrial biopsy. [13] Drotaverine is effectively used in gynecological conditions like dysmenorrhea and nongynecological conditions like renal colic and cholelithiasis. [8] In the studies by Sharma et al and Singh et al, drotaverine when used during labor was shown to accelerate the labor and no adverse effects were seen.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] In literature there are studies where plain NSAIDs were used for pain relief before minor gynecological procedures and compared with placebo, paracervical block, intrauterine lignocaine insertion, local spray of lignocaine gel, but the results were not conclusive. [12][13][14] Various reasons have been cited for this, like cultural factors for pain tolerance, race, diameter of the hysteroscope, etc. There is a paucity of similar studies on Indian women.…”
Section: Discussionmentioning
confidence: 99%